2021
DOI: 10.3389/fonc.2020.593022
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Oncogenic Driver Alteration Associated Immune-Related Prognostic Model for Stage I-II Lung Adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) needs to be stratified for its heterogeneity. Oncogenic driver alterations such as EGFR mutation, ALK translocation, ROS1 translocation, and BRAF mutation predict response to treatment for LUAD. Since oncogenic driver alterations may modulate immune response in tumor microenvironment that may influence prognosis in LUAD, the effects of EGFR, ALK, ROS1, and BRAF alterations on tumor microenvironment remain unclear. Immune-related prognostic model associated with oncogenic driver alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…These results suggest that higher proportions of M1 macrophages, activated mast cells, and activated memory CD4 T cells, and lower proportions of resting mast cells, monocytes, and plasma cells might increase the risk of a poor prognosis in patients with LUAD. Higher immunosuppression and lower immunoreactivity in TME may result in a poorer prognosis among high-risk LUAD patients ( Xu et al, 2020 ). Investigating the characteristics of TME cell infiltration in LUAD patients in relation to different m6A-related-lncRNAs patterns may thus facilitate the development of individualized novel immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that higher proportions of M1 macrophages, activated mast cells, and activated memory CD4 T cells, and lower proportions of resting mast cells, monocytes, and plasma cells might increase the risk of a poor prognosis in patients with LUAD. Higher immunosuppression and lower immunoreactivity in TME may result in a poorer prognosis among high-risk LUAD patients ( Xu et al, 2020 ). Investigating the characteristics of TME cell infiltration in LUAD patients in relation to different m6A-related-lncRNAs patterns may thus facilitate the development of individualized novel immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Several prognostic models for LUAD based on the above techniques have been published, but these models still have limitations. The biomarkers selected had a minimal relationship with tumor proliferation and cannot fully reflect the proliferation potential of LUAD [7][8][9]. The cancer dependence of genes is the basis of prognosis prediction and drug target research.…”
Section: Introductionmentioning
confidence: 99%
“…The multivariate analysis of the LUAD cohort confirmed the DMS system could be an independent factor for patient prognosis. Altogether, the above results indicated that there was indeed a higher heterogeneity of DNA methylation modifications in the tumor immune/alteration microenvironment of LUAD ( 42 ).…”
Section: Discussionmentioning
confidence: 71%